Il romanzo moderno nella poetica del sé di Paul Ricœur (ENTHYMEMA, 2013)
In Ricœur’s thought, the analysis of the modern novel and the birth of the idea of ‘narrative identity’ – one of the crucial notions in the hermeneutics of the self – are tightly connected. Through a reading of different works by the French philosopher, the essay will show the poetical genesis of this idea, and will compare Ricœur’s theory of the modern novel with the major notions on this literary form held in literary criticism and theory.